2017
DOI: 10.1038/s41598-017-10277-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel evidence for complement system activation in chick myopia and hyperopia models: a meta-analysis of transcriptome datasets

Abstract: Myopia (short-sightedness) and hyperopia (long-sightedness) occur when the eye grows too long or short, respectively, for its refractive power. There are currently approximately 1.45 billion myopes worldwide and prevalence is rising dramatically. Although high myopia significantly increases the risk of developing a range of sight-threatening disorders, the molecular mechanisms underlying ocular growth regulation and its relationship to these secondary complications remain poorly understood. Thus, this study me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 100 publications
4
40
0
Order By: Relevance
“…Activation of the complement system may promote remodeling of the extracellular matrix and development of myopia ( Gao et al, 2015 ). In a meta-analysis of eight transcriptome databases for lens-induced or form-deprivation myopia, the authors found significant activation of the complement system in chick models of myopia ( Riddell and Crewther, 2017 ). It has also been noted that the eyes are a hotspot for complement dysregulation ( Riddell and Crewther, 2017 , Skeie and Mahajan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the complement system may promote remodeling of the extracellular matrix and development of myopia ( Gao et al, 2015 ). In a meta-analysis of eight transcriptome databases for lens-induced or form-deprivation myopia, the authors found significant activation of the complement system in chick models of myopia ( Riddell and Crewther, 2017 ). It has also been noted that the eyes are a hotspot for complement dysregulation ( Riddell and Crewther, 2017 , Skeie and Mahajan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…5) as refractive compensation and growth rates normalized. The upregulation in mitochondrial energy pathways over the 10 days of FDMI was not unexpected given previous ultrastructural evidence of abnormal photoreceptor elongation and mitochondrial loss of integrity (Beresford et al 1998;Liang et al 1995;Liang et al 2004), and expression studies providing evidence for altered energy metabolism (Riddell et al 2017;Riddell et al 2016) and oxidative stress (Francisco et al 2015;Riddell & Crewther 2017b) in myopia.…”
Section: Discussionmentioning
confidence: 64%
“…This is an important result as the relationship between complement factors and myopia has only been reported once in humans (Long et al 2013) and in the cells from posterior sclera of experimentally-induced myopia in guinea pigs (Gao et al 2015). More recently, a meta-analysis has suggested a role for the complement system in experimental myopia (Riddell & Crewther 2017b). Notably one of the core genes identified in this pathway was serpin peptidase G (C1 inhibitor; SERPING1), which is reported to function to maintain blood vessel integrity by binding to F12a (not identified in this study) and inhibiting Bradykinin (Davis et al 1986), a protein that promotes inflammation by increasing the permeability of blood vessel walls (Greenwood 1991) and calcium-dependent release of glutamate from astrocytes (Parpura et al 1994).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…There was also a 47-gene overlap with the genes found by Riddell et al to be differentially expressed in the retina of chicks exposed to optical defocus [76], while 292 genes found in mice overlapped with genes found to be differentially expressed in the retina of chicks with lensinduced myopia by Stone et al [77]. Many of the genes that we found to be involved in refractive eye development in this study had been previously implicated in various physiological and pathological processes in the retina.…”
Section: Discussionmentioning
confidence: 66%